KEMAMPUAN BERPIKIR KREATIF SISWA DITINJAU DARI DISPOSISI MATEMATIS - Rizka Mauludin; Fitrianto Eko Subekti (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Mathematical problems sometimes require different ways and different points of view in the process of solving them. This study aims to get an overview of the ability to think creatively by considering the category of mathematical disposition. The research method uses a qualitative descriptive type. Respondents in this study consisted of three students of eleventh grade of SMA Negeri 1 Larangan who were taken by purposive sampling technique based on the results of a mathematical disposition questionnaire. The ability to think creatively is based on the results of tests and interviews on trigonometry material. The results of tests and interviews showed that there were differences in students' creative thinking abilities among them with the result high, medium and low mathematical dispositions. The respondent who has a high disposition can fulfill the indicators of originality, flexibility, fluency and elaboration. The respondent with medium dispositions can fulfill indicators of flexibility and elaboration. Whereas for the respondent with low dispositions they cannot meet the indicators of the ability to think creatively mathematically. Concept understanding and self-confidence factors are thought to be factors that cause mistakes made